Conflicted Antiquities Egyptology, Egyptomania, Egyptian Modernity - Colla, Elliott (Duke University Press, 2007)
Conflicted Antiquities is a rich cultural history of European and Egyptian interest in ancient Egypt and its material culture, from the early nineteenth century until the mid-twentieth. Consulting the relevant Arabic archives, Elliott Colla demonstrates that the emergence of Egyptology-the study of ancient Egypt and its material legacy-was as consequential for modern Egyptians as it was for Europeans. The values and practices introduced by the new science of archaeology played a key role in the formation of a new colonial regime in Egypt. This fact was not lost on Egyptian nationalists, who challenged colonial archaeologists with the claim that they were the direct heirs of the Pharaohs, and therefore the rightful owners and administrators of ancient Egypt's historical sites and artifacts. As this dispute developed, nationalists invented the political and expressive culture of "Pharaonism"-Egypt's response to Europe's Egyptomania.